Mesoporous Materials: Synthesis and electrochemical applications - Saira Kausar; Maria Yousaf; Sadullah Mir; Nasser S. Awwad; Huriyyah A. Alturaifi; Farhan Riaz (Electrochemistry Communications)
Mesoporous materials are the epicentre of numerous scientific innovations with tunable pore size and extensive surface area, harnessing their potential in multiple fields such as electrocatalysis, photocatalysis, and environmental remediation. This review offers a detailed overview of diverse categories, synthesis methods, and various applications of mesoporous materials. Distinct categories of porous materials are thoroughly analyzed, featuring mesoporous silica, ordered mesoporous carbon, mesoporous MOFs, mesoporous metals, and metal oxides. Moreover, different synthesis techniques are explored in this review such as template-assisted methods employing hard and soft templates, sol–gel processing, hydrothermal, and microwave-assisted synthesis showcasing their role in the development of materials with tailored properties. Furthermore, this review delves into numerous applications of mesoporous materials, including their role in energy storage devices, photocatalysis, water splitting for fuel production, environmental remediation, sensing, adsorption, and desalination techniques like capacitive deionization for the treatment of brackish water. This review distinguishes itself by providing a thorough analysis of mesoporous materials, equipped with tables, figures, and diagrams for better understanding, and highlights the significant influence of mesoporous materials on contemporary science and technology.